Providing the right skills to all in China From "made in China" to "created in China - Molnar, Margit (OECD Publishing, 2015)
China has made impressive strides in education in recent decades, even though the accumulation of human capital has lagged behind that of physical capital. Going forward, access to and quality of education will be key to sustain economic convergence with the most advanced economies and to offset the drag exerted by population ageing. This will require addressing a number of problems. Access to pre-school education is still far from universal. Migrants' children as well as rural and poor families are still at a major disadvantage at every step of the education ladder. The focus on rote learning and exams remains excessive. More bridges are needed between vocational and general education. Graduating students often struggle to find a job matching their expectations and employers do not always find the requisite skills. Despite a soaring number of Chinese patents, the quality of most patents is still low and innovation output is weak. Reforms are underway to address these problems but further progress is needed in various areas against the backdrop of rapidly evolving market demands and the development of the knowledge economy. Among the priorities are more and better oriented funding of education, giving greater opportunities to children with a socio-economic or physical disadvantage, reducing the role of after-school tutoring, focusing less on memorisation and more on creativity, enhancing the appeal of the teaching profession, improving students' information on labour market prospects, developing workplace training, making greater use of online education potential, and more effectively nurturing research and innovation. This Working Paper relates to the 2015 OECD Economic Survey of China www.oecd.org/eco/surveys/economic-survey-china.htm
Keywords: Economics; China, People's Republic